Adrenal Crisis - Weismann, Dirk (Deutsche medizinische Wochenschrift (1946), 2025)
According to long-term studies, patients with adrenal insufficiency (AI) exhibit a reduced quality of life and increased mortality. In addition to cardiovascular and malignant diseases, the risk of mortality is particularly increased by adrenal crises. Fatal adrenal crises could be completely prevented by timely intravenous or subcutaneous administration of glucocorticoids. In the case of an established diagnosis of AI, a deterioration in the general condition, gastroenteritis symptoms, exsiccosis and a clinical picture of sepsis must lead to the suspicion of an adrenal crisis. However, the diagnosis is only confirmed by the response to glucocorticoids. So-called check-point inhibitors are becoming increasingly important as a cause of AI. Therefore, AI and adrenal crises continue to pose a challenge for patients, their relatives and the treating physicians.